Derivative Spectrophotometric Methods for Simultaneous Determination of Quercetin and Gentisic acid in Capparis spinosa L. (Baghdad Science Journal, 2024)
Capparis spinosa L. is one of the medicinal plants used in traditional medicine which contains numerous phytochemicals including polyphenolic compounds. Quercetin and gentisic acid are two important phenolic compounds found in plants which display many medicinal properties such as anti-inflammatory, antimicrobial, antioxidant and anticancer. Determination of both compounds together in a binary mixture is not achieved yet with spectrophotometric methods. In this study, two simple, rapid and accurate derivative spectrophotometric methods were developed and used for simultaneous quantification of quercetin and gentisic acid in binary mixtures of Capparis spinosa L. methanolic leaves extract. The first technique relies on the zero-crossing approach (first and fourth order derivatives), while the second approach is based on using ratio spectra and first-order derivative spectrophotometry. The calibration curves of the two derivative spectrophotometric techniques are linear in the concentration ranges of 2.0-30 µg/mL and 4.0-80 µg/mL for quercetin and gentisic acid, respectively, whereas the recovery percentages ranged from 94.06% - 105.98% (quercetin) and 94.29% - 113.37% (gentisic acid). The developed methods were effectively used for the quantitative determination of both phenolic compounds in Capparis spinosa L. leaves.